10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Screening and brief intervention (SBI) is widely recommended to promote detection and early intervention for alcohol and other drug (AOD) use in pediatric primary care (PC). This multi-site randomized effectiveness trial screened 550 adolescent-caregiver dyads for AOD use risk factors in 3 urban PC practices. One hundred forty-eight adolescents at-risk for AOD use problems and their caregivers were enrolled in SBI-A-Standard, which included only adolescents in all intervention activities; or SBI-A-Family, which included both adolescents and caregivers in all SBI activities. Compared with SBI-A-Standard, SBI-A-Family procedures identified and provided intervention to more adolescents at risk for AOD use problems (47% of screened dyads vs 24%). Moreover, SBI-A-Family counseling interventions, although more extensive and resource demanding, were administered to 82% of indicated cases and rated near universally as helpful by adolescents, caregivers, and providers. Results of this study demonstrate added value of family-inclusive SBI models for identifying and addressing youth AOD use in PC.